2006
DOI: 10.1037/0096-1523.32.4.865
|View full text |Cite
|
Sign up to set email alerts
|

Letter position information and printed word perception: The relative-position priming constraint.

Abstract: Six experiments apply the masked priming paradigm to investigate how letter position information is computed during printed word perception. Primes formed by a subset of the target's letters facilitated target recognition as long as the relative position of letters was respected across prime and target (e.g., "arict" vs. "acirt" as primes for the target "apricot"). Priming effects were not influenced by whether or not absolute, length-dependent position was respected (e.g., "a-ric-t" vs. "arict"/"ar-i-ct"). Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
322
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(363 citation statements)
references
References 47 publications
29
322
4
2
Order By: Relevance
“…We also considered it important to include primes created by various amounts of insertion (e.g., pragkise-PRAISE) and deletion (e.g, prse-PRAISE; also known as superset and subset primes, respectively, e.g., Grainger et al, 2006;. These conditions provide evidence regarding the relative importance of different positions, the flexibility of positional representation, and the balance of positive and negative evidence in lexical matching.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We also considered it important to include primes created by various amounts of insertion (e.g., pragkise-PRAISE) and deletion (e.g, prse-PRAISE; also known as superset and subset primes, respectively, e.g., Grainger et al, 2006;. These conditions provide evidence regarding the relative importance of different positions, the flexibility of positional representation, and the balance of positive and negative evidence in lexical matching.…”
Section: The Present Studymentioning
confidence: 99%
“…This concern is reflected in explicit computational models (e.g., Adelman, 2011;Davis, 2010;Norris & Kinoshita, 2012), as well as a wealth of experimental research, much of it using the masked form priming paradigm developed by Forster and Davis (1984, ;Forster, Davis, Schoknecht, & Carter, 1987). In these experiments (e.g., Davis & Bowers, 2006;Davis & Lupker, 2006;Grainger, Granier, Farioli, Van Assche, & van Heuven, 2006;Perea & Lupker, 2003), the presentation of a target stimulus for a lexical decision is preceded by a brief presentation of a potentially related (nonword) prime stimulus. From the extent that 1.4.2 responses to a word target are faster following a related nonword prime than following an unrelated prime, researchers make inferences regarding similarity between the processing evoked by the related prime and the processing evoked by a veridical presentation of the target.…”
Section: Introductionmentioning
confidence: 99%
“…When the overlap dimension was purely formal, no priming effects were observed (e.g., tinsel -TIN). In contrast, some studies have reported orthographic priming effects at short stimulus onset asynchronies (SOAs) under masked priming conditions (e.g., Chateau, Knudsen, & Jared, 2002;Forster & Azuma, 2000;Grainger, Granier, Farioli, Van Assche, & van Heuven, 2006). In three masked priming experiments manipulating prime duration, Forster and Azuma (2000) compared priming effects between a) prefixed words sharing a bound stem (submit -PERMIT), b) a prefixed word and its free stem (fold -UNFOLD), and c) unrelated words sharing their (non-morphological) final graphemes (shallow -FOLLOW).…”
mentioning
confidence: 97%
“…In this way, we can gather information about lett er-level processing while minimizing the infl uence of higher-level phonological and semantic processes. Th e assumption here is that during visual word recognition, some form of lett er-level processing must be performed before higher order codes come into play (Grainger, Granier, Farioli, Van Assche, & van Heuven, 2006;Grainger & van Heuven, 2003).…”
Section: Introductionmentioning
confidence: 99%